The Indus: lost civilizations - Robinson, Andrew (London Reaktion Books Ltd, 2016)
The Indus civilization flourished for half a millennium from about 2600 to 1900 BCE, when it mysteriously declined and vanished from view. It remained invisible for almost four thousand years, until its ruins were discovered in the 1920s by British and Indian archaeologists
Keywords: Indus civilization; Asia--Indus River Valley